A Simple Model for Describing Non-Adherence to Medication in Tuberculosis Patients in a Tropical Area, Indonesia - Zahroh, Chilyatiz; Ainiyah, Nur; Soleha, Umdatus; Sudiana, I Ketut; Yusuf, Ah (Jurnal Keperawatan Soedirman, 2023)
Indonesia has the second-highest number of tuberculosis (TB) cases in the world. Many TB patients did not take their medicine at health care centers causing an increase in taking medication. This study aimed to develop a simple model for describing non-adherence to medication in TB patients. This study used an analytical with a cross-sectional approach. The following criteria were used in selecting the respondent: adolescent, able to read and write, and willingness to be a respondent. A total of 93 participants were recruited randomly. Data were collected through questionnaires and analyzed using logistic regression. The predisposing factors were knowledge, attitude, belief (p = 0.000), trust (p = 0.013), and values (p = 0.001). Family support (p = 0.034) and healthcare personnel support (p = 0.022) were reinforcing factors. The enabling factor was the healthcare facility (p = 0.000). This study found that the most dominant factor is knowledge (B = 56.4). The model was Logit (Pi) = 22.363 + 56.4 knowledge (1) + 22.56 belief (1) + 2.9 family support (1) + 0.577 healthcare support (1) + 0.061 healthcare facility (1). This study suggests that TB patients’ knowledge must be increased to improve their TB treatment and management.